Peran Buku Guru Pada Pembelajaran Pendidikan Agama Buddha dan Budi Pekerti di Kecamatan Gangga Lombok Utara - Jayanto; Sentot; Aryanto Firnadi (STAB Kertarajasa, 2023)
This study aims to describe the implementation of the Buddhist Religious Education and Moral Education teacher's guidebooks in three schools (high school, junior high school, and elementary school) in the Gangga District, North Lombok. Another objective is to identify the constraints or challenges in implementing these teacher's guidebooks and to find solutions or strategies to enhance their usage. The research employs a qualitative approach using interview, observation, and documentation as instruments. Data analysis is conducted using the Miles and Huberman model through data condensation, display, and conclusion drawing or verification stages. The results indicate that the implementation of the teacher's guidebooks in the three schools has been effective. Proficient teachers have successfully applied the guidebooks, which contain learning steps, objectives, and functions. Nevertheless, the usage of these guidebooks still faces challenges. Insufficient teacher's guidebook and student textbook facilities in schools, uneven book distribution from the government, and inadequacies in the content of the teacher's guidebooks are notable hindrances in the learning process. Therefore, solutions or strategies are needed to enhance the use of the Buddhist Religious Education and Moral Education teacher's guidebooks. Possible solutions or strategies involve increasing support from schools, the Education Office, and the government in monitoring the distribution of teacher's guidebooks and student textbooks. Subject Teacher Professional Development (STPD) could organize training related to teacher's guidebooks through workshops, seminars, panel discussions, symposiums, and workshops.